Transforming Word of Mouth: The Role of EMR Design, Customer Support, and Security in Health Facilities Using Pinus Software in Surabaya and Pasuruan - David Irawan Winoto; Yolanda Soedibyo (Universitas Pelita Harapan, 2024)
The healthcare industry's ongoing technological advancements make keeping electronic medical records a must. All healthcare facilities must use electronic medical records that are linked to SATUSEHAT, under rules issued by the Ministry of Health of the Republic of Indonesia. For software businesses that offer electronic medical record software, this creates enormous opportunity. The goal of this study is to examine how various aspects of the overall electronic medical records service quality, such as design, security/privacy, and customer support, affect customer satisfaction and trust, which in turn affect positive word of mouth among PINus Software users who use electronic medical records in Surabaya and Pasuruan. This study used a quantitative survey approach, gathering information from five healthcare facilities to gain 175 respondents, which were analyzed using SPSS. These results demonstrate variable customer support has no effect, two independent variables have a considerable impact. The study's conclusions highlight the significance of electronic medical record design, security/privacy, all of which have been shown to have a major impact on overall electronic medical record service quality, which in turn affects customer satisfaction and trust, which in turn affects word-of-mouth.